Forgotten roots of Japanimation: In praise of shadows - Sharp, Jasper (Film International, 2006)
There cannot be many by now who are not acquainted with the term anime. If so, it is certainly not for a lack of exposure to what can now be seen as Japan's top pop-cultural export.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9maWluLjQuMy4zMA